2019
DOI: 10.1055/s-0039-1695707
|View full text |Cite
|
Sign up to set email alerts
|

Distal Metaphyseal Osteotomy Allows for Greater Ulnar Shortening Compared to Diaphyseal Osteotomy for Ulnar Impaction Syndrome: A Biomechanical Study

Abstract: Purpose To compare the biomechanical characteristics between diaphyseal and metaphyseal ulnar-shortening osteotomy with respect to (1) maximal shortening achieved at each osteotomy site and (2) force required to achieve shortening at each site. Methods Nine fresh frozen cadaveric upper extremities were affixed through the proximal ulna to a wooden surgical board. A metaphyseal 20-mm bone wedge was resected from the distal ulna and sequential shortening was performed. A load cell was attached to a dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…Moreover, we found that metaphyseal USO generally had a shorter operative time than diaphyseal USO. The shorter operation time in the metaphyseal USO group indicated that this type of osteotomy is easier to perform, which could be related to several points, as Owing to the abundant blood supply and less resistant to osteotomy, a metaphyseal USO is considered to provide better bone healing potential than a diaphyseal USO [28], which is consistent with our findings. Despite these theoretical advantages, bony union was achieved in all patients in this study, regardless of the surgical technique, in line with previous findings [8,26,27].…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, we found that metaphyseal USO generally had a shorter operative time than diaphyseal USO. The shorter operation time in the metaphyseal USO group indicated that this type of osteotomy is easier to perform, which could be related to several points, as Owing to the abundant blood supply and less resistant to osteotomy, a metaphyseal USO is considered to provide better bone healing potential than a diaphyseal USO [28], which is consistent with our findings. Despite these theoretical advantages, bony union was achieved in all patients in this study, regardless of the surgical technique, in line with previous findings [8,26,27].…”
Section: Discussionsupporting
confidence: 88%
“…However, evidence for ulnar-positive variance at or ≥5 mm is currently lacking, even though a cadaveric study suggests that DMUSO may have a similar or longer osteotomy distance compared with USO. 61 Researchers observed that DMUSO was more effective than USO in relieving pain and Quick-DASH scores were higher. 62 Additionally, due to the distal location of the osteotomy in DMUSO, it reduced the separation and traction effects of the interosseous membrane on the osteotomy ends.…”
Section: Introductionmentioning
confidence: 99%
“…Transverse osteotomy is relatively simple, but the contact area of both ends of the fracture is small, and is prone to rotation displacement, so the fracture healing time is long. The contact area of both ends of V‐shaped and trapezoidal osteotomy fractures is large, and the anti‐rotation force is enhanced, but the operation is more complicated, the operation time is long, and the two ends of the fracture are prone to malalignment 9 . However, oblique osteotomy is easy to perform, with a large contact area and strong anti‐rotation force, so it is widely used in the clinic 10 .…”
Section: Introductionmentioning
confidence: 99%